Comparison of Ablation Volume Between Emprint® and Mimapro® Systems for Hepatocellular Carcinoma –A Preliminary Study - Ishikawa T; Hasegawa I; Hirosawa H; Honmou T; Sakai N; Igarashi T; Yamazaki S; Kobayashi T; Sato T; Iwanaga A; Sano T; Yokoyama J; et al. (Journal of Hepatocellular Carcinoma, 2023)
Toru Ishikawa,1 Iori Hasegawa,2 Hiroshi Hirosawa,2 Tsubasa Honmou,2 Nobuyuki Sakai,2 Takanori Igarashi,1 Shun Yamazaki,1 Takamasa Kobayashi,1 Toshifumi Sato,1 Akito Iwanaga,1 Tomoe Sano,1 Junji Yokoyama,1 Terasu Honma1 1Department of Gastroenterology, Saiseikai Niigata Hospital, Niigata, Japan; 2Department of Clinical Engineering, Saiseikai Niigata Hospital, Niigata, JapanCorrespondence: Toru Ishikawa, Department of Gastroenterology, Saiseikai Niigata Hospital, Teraji 280-7, Niigata, Japan, Tel +81-25-233-6161, Fax +81-25-233-8880, Email toruishi@ngt.saiseikai.or.jpBackground: Microwave ablation (MWA) is a standard percutaneous local therapy for hepatocellular carcinoma (HCC). Next-generation MWA is reported to create a more spherical ablation zone than radiofrequency ablation (RFA). We compared the ablation zone and aspect ratio of two 2.45 GHz MWA ablation probes; Emprint® (13G) and Mimapro® (17G). We compared the ablation zone to the applied energy after MWA in patients with hepatocellular carcinoma (HCC). Furthermore, we investigated local recurrence.Materials and Methods: We included 20 patients with HCC, with an average tumour diameter of 33.2 ± 12.2 mm, who underwent MWA using Emprint®, and 9 patients who underwent MWA using Mimapro® with an average tumour diameter of 31.1 ± 10.5 mm. Both groups underwent the same ablation protocol using the same power settings. The images obtained after MWA showed the treatment ablation zone and aspect ratio, which were measured and compared using three-dimensional image analysis software.Results: The aspect ratios in the Emprint® and Mimapro® groups were 0.786 ± 0.105 and 0.808 ± 0.122, respectively, with no significant difference (p = 0.604). The ablation time was significantly shorter in the Mimapro® group than in the Emprint® group, and there was no significant difference in the frequency of popping or the ablation volume. There were no significant differences in local recurrence between the two groups.Conclusion: There was no significant difference in the aspect ratios of the ablation diameter, and the ablation zone was almost spherical in both cases. Mimapro® at 17G was less invasive than Emprint® at 13G.Keywords: hepatocellular carcinoma, microwave ablation, ablation zone